Studi Daya Dukung Fisik Wisata Bahari Usat Liberty Wreck Di Desa Tulamben Bali - Rizaldy, Mohammad Febrian Gamma; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 7 No 1 (2019): VOL 7, NO 1 (2019): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2019)
Marine tourism activities are feared to give pressure through tourists’ crowds who visit to USAT Liberty Wreck as the main attraction in Tulamben. The utilization should be not undermining the quality of physical attraction and the tourist comfortness. Research is conducted to find out the ability of physical carrying capacity on this popular dive spot. Qualitative and quantitative data are collected by observation in land and underwater, depth interview with interviewess and literatures study. Then Data is processed by stages: (1)data reduction, (2)data explanation and (3)verification. Research begins by mapping of marine tourism activity in Tulamben. The result of calculating physical carrying capacity in USAT Liberty Wreck is 306 person consisting of 102 dive guide and 204 tourist in static condition on diving space at same time, compared to the amount of tourist arrival in 2014 for 173 person per day. In conclusion, tourist arrival does not exceed capability of physical carrying capacity USAT Liberty Wreck. Key words: Pyshical Carrying Capacity, Marine Tourism, USAT Liberty Wreck